A REVIEW OF RESEARCH ON THE IMPACTS OF TEXTING ON VOCABULARY AMONG SECOND LANGUAGE LEARNERS - Soh, Or-Kan; Hazita, Azman; Isnin, Izzammuddin (Institute of Advanced Engineering and Science, 2020)
This paper provides the critical review of the impacts of texting on vocabulary among students from various range of ages, level of studies and background. Emergence of communication through modern modes of communication such as texting has greatly influenced the written communication among students. This impact of texting can also be traced from their academic writings. So far, there is lack of review studies with the focus on the impact of texting on vocabulary. Its consequential impact on the standard language has acquired greater importance. This studies also determine the relationship between the correlation of use of Instant Messaging and Text Messaging and the English grammar, vocabulary and spelling of the students. In total, 50 studies published between 2006 to 2019 and 20 indexed journals were analysed. The main findings from this review provide the impacts of texting on vocabulary among students. Furthermore, the paper discusses trends and the vision towards the future and opportunities for the further research in texting using Instant Messaging and Text Messaging.